Photosynthetic and growth response of C3 and C4 subspecies of Alloteropsis semialata to nitrogen-supply - Abraham, Trevor Ian (Rhodes University, Faculty of Science, Botany Department, 2008)
The greater photosynthetic nitrogen use efficiency (PNUE) of C4 compared with C3 plants may explain the relative success of C4 grasses in nutrient poor environments. This study compared the responses in photosynthetic parameters, leaf nitrogen and biomass allocation between the C3 and C4 subspecies of Alloteropsis semialata supplied soil nitrogen at three levels. Photosynthesis was assessed by means of CO2 response curves and the leaf nitrogen content assayed. Plants were destructively harvested, leaf areas determined and the dry biomass of functional plant components was measured. Results confirmed that the higher PNUE of C4 plants allowed them to accumulate more biomass than C3 plants at the high nitrogen level, despite smaller leaf areas. The greater productivity of C4 plants enabled them to invest more in storage and sexual reproduction than in leaves when compared to the C3 plants. In contrast the C3 plants invested biomass in less efficient and more nitrogen demanding leaves and bigger root systems. PNUE and photosynthetic rates were not significantly affected by nitrogen-limitation in either subspecies and the major response was a decrease in biomass accumulation and an increase in biomass allocation to roots. This altered root to shoot ratio was accompanied by a lowered allocation to sexual reproduction in the C4 subspecies, but an unaltered allocation to leaves, while in the C3 subspecies there was a decrease in leaf allocation. In a further experiment, the C4 subspecies was supplied three levels of nitrogen provided as nitrate, or alternatively as ammonium plus nitrate, and leaves were excised to within 5 cm of the ground at the start of treatment. Prior to flowering, photosynthesis was assessed by means of CO2 response curves and the plants were destructively harvested. Leaf areas and the dry biomass of functional plant components were determined, and at levels of nitrogen supply higher than those found in savanna soils the rate of photosynthesis was increased. Leaf re-growth was reduced by severe nitrogen limitation and co-provision of nitrate and ammonium had no significant effect other than increased tillering. Both subspecies of Alloteropsis semialata are adapted to nutrient poor environments and maintain photosynthetic rates by reducing leaf area. The C4 subspecies is likely to show greater resilience in disturbance-prone environments by exploiting its higher PNUE to allocate greater resources to storage and sexual reproduction, while the C3 subspecies is usually found in environments with closed canopies which favour vegetative growth, and allocate greater resources to leaves and roots.
Keywords: Photosynthesis; Plants -- Effect of nitrogen on; Growth (Plants); Plant ecology